Technical skills in complex tennis situations: Dutch talented players U15 compared to players U17 - Kolman, N. S.; Huijgen, B. C. H.; Visscher, C.; Elferink-Gemser, M. T. (Frontiers in Sports and Active Living, 2023)
Introduction: Technical skills in complex situations appear crucial for progress towards elite tennis performance. However, it is unknown how these skills develop in different age categories in a group of talented youth players. The aim of this study is to evaluate possible differences in technical skills among Dutch talented youth tennis players U15 compared to U17.